Malnutrition Assessment of Chronic Obstructive Pulmonary Disease Patients (Medical Forum Monthly, 2024)
Objectives: To assess the prevalence and severity of malnutrition among COPD patients along with the effect of dietary intervention on the disease outcome. Study Design: This was an interventional, Quasi- experimental study. Place and duration of Study: The study was conducted at Department of Medicine and Department of Chest Diseases, Jinnah Hospital, Lahore. Total duration was one year from April 2009 to March 2010. Materials and Methods: Sample Size: 100 patients with COPD were investigated. Sampling: Purposive Non-probability sampling. Results: Majority of the patients were in the age range 50 – 70 years with more males than females. 97% patients had a positive tobacco smoking history. 57 - 78% of the patients included in the study were found to be malnourished, out of which 65 - 68% were moderately malnourished and 10% were severely malnourished according to SGA rating and BMI. There was a strong correlation between COPD staging and malnourishment. 54% patients with stage III COPD were malnourished while 90% patients with stage IV were found to be malnourished. Conclusion: Malnutrition is invariably observed in COPD patients and is more frequent and more severe in patients with advanced stage disease. Patients with COPD might benefit from a dietary intervention both in terms of pulmonary functions and nutritional state, which might have beneficial effects on prognosis.